Factors Determining Successful Exclusive Breastfeeding on Working Mothers in Indonesia: An Exploration by Using Positive Deviance Concept - Melinda Mastan; Endang Laksminingsih Achadi (Indonesian Journal of Public Health Nutrition, 2021)
Despite the fact that exclusive breastfeeding brings a lot of benefits for infants and mothers, breastfeeding rates in Indonesia remain low, standing only at 42% of all infants aged 0-5 months in 2012. This study aims to apply the positive deviance concept to explore the factors determining the success of exclusive breastfeeding among mothers in the high risk group in Indonesia. The study uses the cross-sectional, DHS 2017 data on 1.178 mothers with 0-5 months old infants in Indonesia. Chi-square and multiple logistic regression test with 95% confidence intervals are used in identifying the factors associated with exclusive breastfeeding. Maternal employment is shown to be the most significant risk factor in preventing mothers to breastfeed exclusively. Furthermore, the data suggest that, out of 376 working mothers, 45,5% can be identified as positive deviants – those succeeding in implementing exclusive breastfeeding. The study finds ANC visits, PNC visits, and economic status display significant association with exclusive breastfeeding among working mothers. In the sample, ANC visit is the dominant factor associated with exclusive breastfeeding (OR: 1,831; 95% CI: 1,075-3,118). Completion of ANC and PNC visits should be taken to consideration in improving exclusive breastfeeding rate among working mothers in Indonesia.